Hubungan Asupan Vitamin B1 (Tiamin) Terhadap Kadar Glukosa Darah Pada Lansia Di Posyandu Lansia Ngudi Waras Desa Blulukan Kecamatan Colomadu, Karanganyar, Jawa Tengah - Nuringtyas, Irin Shofiani; , Dwi Sarbini, S.ST., M.Kes (2016)
Introduction :On the elderly one of the factors causing the rise in blood glucose levels are the intake of food. High consumption of thiamine can decrease blood glucose levels. Bassed on the results of research in post service elderly at Blulukan with high blood glucose levels diagnosis by 46,2% of the elderly. Objective :This study aims to analyse the correlation of vitamin B1 (thiamine) intake with glucose blood levels in elderly peoples at integrated post service elderly NgudiWaras in the Blulukan village, Colomadu, Karanganyar, Central Java. Research Method :This research was included analytic observational with cross sectional approarch method. The samples were obtained from a population that completing the criteria of inclusion and exclusion some of 36 elderlies. The method that used is concecutive sampling method. Intake of thiamine obtained from the average of semi-quantitative FFQ for a month period and showed in terms of mg, while blood glucose levels as obtained using spectrophotometric method. The normality data test using Shapiro Wilk and correlation test using Rank Spearman test. Result :From the results of the univariat analysis got blood glucose levels when majority of the respondents are normal as much as 35 respondents (97,2%) and vitamin B1 (thiamine) intake majority of the respondentsare less as much as 19 respondents (52,7%). From spearman rank test shows the result of intake vitamin B1 (thiamine) analysis with blood glucose levels with the value of p=0,655 (>0,05) which means no correlation intake vitamin B1 (thiamine) with blood glucose levels. Conclusion : There is no correlation of vitamin B1 (thiamine) intake with glucose blood levels in elderly peoples at integrated post service elderly NgudiWaras in the Blulukan village, Colomadu, Karanganyar, Central Java